Aplikasi Sistem Informasi Geografis (SIG) Untuk Kajian Fluktuasi Muka Air Tanah dan Karakteristik Akuifer di Kecamatan Denpasar Barat - LESTARI, NI LUH AYU DANA; TRIGUNASIH, NI MADE; WIYANTI, WIYANTI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
The Application of Geographic Information System (GIS) for Study of Groundwater Fluctuations and Characteristics of Aquifers at West Denpasar District   Communities that have not been served by PDAM as much as 47.62%, use ground water to fulfill their clean water needs. The purpose of this study was to determine the distribution of dug wells, distribution of groundwater surface, fluctuations, flow direction and characteristics of aquifers in West Denpasar Subdistrict. This research was carried out by descriptive quantitative method. Analysis was carried out from survey data by using ArcGIS software. The results showed that the highest number of dug wells was found in Pemecutan Klod Village (31,25%). Groundwater surface depth in the dry season was 84.38% classified into 0-5 m class and in the rainy season 90.63% also classified as 0-5 m class too. Almost all of the southern West Denpasar Subdistrict has 0-5 m fluctuations. Groundwater in the West Denpasar Subdistrict is predicted to flow to the South, Southeast and Southwest. There are two types of aquifers in West Denpasar Subdistrict that is shallow aquifers and deep aquifers. Shallow aquifers are at 2-20 m depth with a maximum thickness of 18 m and are composed of passive and breccia material. Deep aquifers are found at 12-24 m depths with a minimum thickness of 12 m and are composed of passive and tufa material. It is estimated that both types of aquifers are good aquifers.